2009
DOI: 10.2174/1876822900902010001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of IIEF-5 for Reporting Erectile Dysfunction Following Nerve-Sparing Radical Retropubic Prostatectomy

Abstract: Abstract:Introduction: Increased detection of organ-confined prostate cancer has led to an increased demand for nervesparing surgery. Most studies of erectile dysfunction (ED) following nerve-sparing radical prostatectomy (RRP) use single-item assessment, and potency rates differ widely among various groups. We aimed to investigate the use of the IIEF-5, a validated questionnaire, for reporting ED following RRP. Aims: To study the use of the IIEF-5 questionnaire in the evaluation of post-RRP ED, and to find po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Previous studies demonstrated the good validity and reliability of this questionnaire when it was used in RP recipients [20].…”
Section: Sexual Function Questionnairementioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies demonstrated the good validity and reliability of this questionnaire when it was used in RP recipients [20].…”
Section: Sexual Function Questionnairementioning
confidence: 81%
“…Impotence occurs in 25% to 100% of patients after prostatectomy [14][15][16][17][18]. In fact, 80% to 90% of patients reported diffi culty with erections after prostatectomy [10,19], and previous studies have indicated that the recovery of sexual function may take up to two years after RP [20][21][22][23], with 60% of men still reporting sexual dysfunction two years after RP [19,24,25]. However, another study conducted by Zielinski [2], showed that fi ve years after a prostate cancer diagnosis and the RP procedure, 79.3% of men continued to experience sexual dysfunction.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IIEF‐5 was developed by Rosen et al (1999) to identify and describe the severity of erectile dysfunction, with possible scores ranging from 5 to 25 (Rosen et al , 1999; Rhoden et al , 2002). Albersen et al , (2009) indicated that the IIEF‐5 questionnaire is valid, accurate and reliable and is an excellent instrument for reporting on erectile function following RP. The Cronbach's α in this study was 0·86, 0·88, 0·77, 0·90 and 0·92 at baseline (time 1), time 2, time 3, time 4 and time 5, respectively, after RP.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1980s, many urologists have employed an anatomical approach to modify their surgical procedures in an effort to diminish these complications. Since Walsh et al (1983) introduced the nerve‐sparing modification to RP, which allowed them to avoid injuring the neurovascular bundles (NVBs) that contain the cavernous nerves and vessels and to thereby preserve erectile functions, several studies have evaluated the effects of nerve‐sparing on the complications observed after RP (Catalona and Bigg, 1990; Talcott et al , 1997; Horie et al , 1999; Lee et al , 2003; Curto et al , 2006; Nakiri et al , 2008; Albersen et al , 2009).…”
Section: Introductionmentioning
confidence: 99%